2003
DOI: 10.1002/mop.10761
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐frequency planar monopole antenna for GSM/DCS/PCS/WLAN operation

Abstract: A novel planar monopole antenna capable of multi‐frequency operation at about 900, 1800, and 2450 MHz is presented. The monopole antenna occupies a small area of 6.5 × 50 mm2, and is easy to construct with low cost by printing on an FR4 substrate. The monopole antenna can be mounted perpendicularly to the system circuit board of a communication device so that a low profile to the system ground plane will result. In addition, the obtained impedance bandwidths of the proposed antenna at about 900, 1800, and 2450… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 3 publications
1
25
0
Order By: Relevance
“…Note that there are two ground planes in this design: one bottom ground and one upper ground, both with the same size of 40 ϫ 75 mm 2 , which is a reasonable size for practical folder-type mobile phones. The upper ground usually accommodates the loudspeaker and the display, and also functions as the cover of the folder-type mobile phone.…”
Section: Antenna Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Note that there are two ground planes in this design: one bottom ground and one upper ground, both with the same size of 40 ϫ 75 mm 2 , which is a reasonable size for practical folder-type mobile phones. The upper ground usually accommodates the loudspeaker and the display, and also functions as the cover of the folder-type mobile phone.…”
Section: Antenna Designmentioning
confidence: 99%
“…Planar monopole antennas mounted perpendicularly to the system ground plane of a wireless handheld device have been demonstrated [1,2]. In order to achieve good impedance matching for frequencies across the desired operating bands, for example, the global system for mobile communication (GSM, 890 -960 MHz), digital communication system (DCS, 1710 -1880 MHz), and personal communication system (PCS, 1850(PCS, -1990 MHz) bands, this kind of planar monopole antenna needs to be mounted with a certain distance (about 5-10 mm) to the system ground plane, which greatly increases the antenna height from the system ground plane.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, n ϭ 1 (for the upper patch), and n ϭ 2 (for the lower patch). The dual-band PIFA is designed for the 900-MHz and 1800-MHz frequency bands [6]. The dimensions are: l 1 ϭ 37 mm, w 1 ϭ 30 mm (top patch); l 2 ϭ 34 mm, w 2 ϭ 30 mm (bottom patch); gap between patches ϭ 5 mm; top patch height ϭ 11 mm; shorting-strap width ϭ 3 mm with 2-mm gap; and semi-miniaturized type-A (SMA) feed-pin coordinates x f ϭ 15 mm, y f ϭ 3.4 mm.…”
Section: Designmentioning
confidence: 99%
“…He et al [5] presented a W-CDMA PIFA, which covers the 250-MHz bandwidth from 1920 to 2170 MHz. P. L. Teng et al [6] reported a multi-frequency planar monopole antenna for GSM/PCS/WLAN operation. S. Yarasi et al [7] proposed a single-feed dual-band PIFA with U-shaped and L-shaped slots for GPS and W-CDMA operations.…”
Section: Introductionmentioning
confidence: 98%